Evidence-based cancer care: assessing guideline adherence of multidisciplinary tumor board recommendations for breast and colorectal cancer in a non-academic medical center - Carl-Stephan Leonhardt; Leopold Lanzenberger; Raphael Puehringer; Ulla Klaiber; Irene Hauser; Oliver Strobel; Gerald Prager; Martin Bodingbauer (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Multidisciplinary tumor boards (MTB) are associated with improved outcomes. Yet, most patients in Western countries receive cancer care at non-academic medical centers. Guideline adherence of MTB recommendations in non-academic medical centers as well as factors contributing to non-adherence remain largely unexplored. Methods This retrospective study followed the STROBE recommendations. All cases discussed at the MTB of the Landesklinikum Baden-Moedling, Austria, were eligible for inclusion. Guideline non-adherence was assessed by two reviewers independently using the AWMF S3 guidelines. Factors associated with guideline non-adherence were investigated using multivariable ordinal regression. Results In total, 579 patients were included in the final analysis: 486 were female (83.9%) and 93 were male (16.1%), with a median age of 70 years (IQR 60–80). Most had breast cancer (n = 451; 77.9%), while 128 had colorectal cancer (22.1%). Complete adherence to guidelines was observed in 453 patients (78.2%), major deviations in 60 (10.4%), and minor deviations in 66 (11.4%) patients. Non-adherence was primarily due to patient preferences (n = 24; 40.0%), lack of surgical treatment recommendation (n = 24; 40.0%), and comorbidities (n = 9; 15.0%). After adjusting for relevant variables, predictors of non-adherence included older age at diagnosis (OR 1.02, 95% CI 1.00–1.04), colorectal cancer (OR 3.84, 95% CI 1.99–7.42), higher ECOG status (OR 1.59, 95% CI 1.18–2.16), and a more recent MTB conference (OR 1.20, 95% CI 1.03–1.41). Conclusion Overall, guideline adherence was high for colorectal and breast cancer and comparable to results from academic medical centers. However, results need to be confirmed in other tumor entities.